Multiple Alfvén eigenmodes induced by energetic electrons and nonlinear mode couplings in EAST radio-frequency heated H-mode plasmas. (8th March 2021) - Zhao, N.; Bao, J.; Chen, W.; Shi, T.H.; Wang, Z.X.; Yan, N.; Liu, S.C.; Liu, H.Q.; Zang, Q.; Lin, S.Y.; Wu, X.H.; Chu, Y.Q.; et al.
Abstract: Multiple electromagnetic coherent modes with frequencies f ∼ 20–300 kHz and toroidal mode numbers n = 1 and n = 2 have been observed and investigated in radio-frequency heated H-mode plasmas of the EAST tokamak. The experimental results show that the two main branches of these coherent modes are driven by energetic electrons (EEs), which are produced in the processes of radio-frequency current drive and heating. Bicoherence analysis indicates that there are strong nonlinear mode interactions between the two branches (mother waves), i.e. one is in the low-frequency range of f ∼ 20–50 kHz and the other one is in the high-frequency range of f ∼ 120–250 kHz, and their nonlinear couplings can generate many harmonics (daughter waves). Both coherent modes propagate poloidally along the electron diamagnetic drift direction. The gyrokinetic eigenvalue simulations support the view that both the low-frequency and the high-frequency coherent modes observed in EAST are Alfvén eigenmode (AE) type, and the kinetic effects of background plasmas and EEs are responsible for the formation and excitation of AEs, respectively. The low-frequency coherent mode is identified as the kinetic beta-induced Alfvén eigenmode located in the edge, and the high-frequency coherent mode is radially global, which is characterized by a toroidal Alfvén eigenmode (TAE) in the core and also has the components of a kinetic TAE and ellipticity-induced Alfvén eigenmode in the outer region due to the large downshift of the Alfvén continuum gap from the core to the edge in H-mode discharges.